High Expression of Lysophosphatidic Acid Induces Nerve Injury in LSS Patients via AKT Mediated NF-κB p65 Pathway - Guiliang Zhai; Wenfei Liang; Yongjun Xu (Frontiers Media S.A., 2021)
Lumbar spinal stenosis (LSS) is a spinal degenerative disease, complicated with nerve injury. Lysophosphatidic acid (LPA), a kind of glycerophospholipid molecule is elevated in the initial stages of neural injury. This research aimed to investigate the patho-mechanism of nerve injury caused by LPA in LSS patients. Twenty-five LSS patients and fifteen idiopathic scoliosis patients (without neurological symptoms) were recruited from Xianyang Central Hospital of Shanxi Province. We measured the concentration of LPA in cerebrospinal fluid samples of all subjects. Different concentrations (0.1, 1, and 10 mol/L) of LPA were used to stimulate Rat Neurons-spinal cord (RN-SC) cells. The effects of LPA on cell injury was detected by MTT and LDH (lactate dehydrogenase) assay. Cell apoptosis was determined by FCM (flow cytometry) and TUNEL staining. The changes in the expression of key proteins involved in Akt mediated NF-κB p65 pathway intervened by LPA were determined by western blot. RN-SC cells were pretreated with JSH-23 (NF-κB inhibitor) before LPA exposure, followed by cell apoptosis measurement. The concentration of LPA in LSS patients was notably higher than that in control patients (p < 0.01). The level of LPA was positively correlated with the severity of LSS. LPA treatment induced RN-SC cells displaying oval or rounded cell body with degenerated protrusion dose dependently. In addition, LPA decreased RN-SC cell viability and promoted cell apoptosis in a dose-dependent manner. LPA initiated Akt phosphorylation, IKB phosphorylation, and NF-κB nuclear translocation in a dose-dependent manner. However, JSH-23 (NF-κB inhibitor) pre-treatment prevented effects of LPA. The high levels of LPA induced nerve injury by reducing the viability of RN-SC cells and promoted cell apoptosis through Akt mediated NF-κB p65 signaling pathway. LPA might be a new therapeutic target for relieving nerve injury in LSS patients.